PENGARUH KETEPATAN WAKTU PELAPORAN, DEFAULT RISK, DAN POLITICAL CONNECTION TERHADAP KUALITAS LABA - Lungkang, Fera Anastasia; Muslih, Muhamad (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.09.TAHUN 2020DO - 10.24843/EEB.2020.v09.i09.p01, 2020)
The earnings quality is an image of earning that do not have any uninterruptions. The earnings quality information is information that can influence investor's decision. Strong market reaction which is investor's response will be reflected in high earnings response coefficient (ERC) that shows the quality of the company's profit. This research aims to determine the effect of timeliness, default risk, and political connection on earnings quality, both simultaneously and partially. The method that used in this research was purposive sampling and obtain of 115 samples from 23 companies with period of 2014-2018. The regression model of this research used panel data regression. The results shown timeliness, default risk, and political conncetion are simultaneously influential on earnings quality. Partially, political connection negatively affects on earnings quality.